Hydrological response of loess slopes with reference to widespread landslide events in the Heifangtai terrace, NW China. (March 2019) - Peng, Dalei; Xu, Qiang; Zhang, Xianlin; Xing, Huilin; Zhang, Shuai; Kang, Kai; Qi, Xing; Ju, Yuanzhen; Zhao, Kuanyao
Graphical abstract: Highlights: Three groundwater domes are found in the center and eastern part of the Heitai terrace. The hydrological processes are characterized by multi-temporal 2D ERT and sensors. Landslide deposits block the seepage and result in local groundwater level rising. Landslide type and magnitude are affected by groundwater seepage and movement. Abstract: In the Heifangtai terrace, NW China, flooding irrigation is common for the cropland production and has increased the groundwater table by 20–30 m over the past five decades. It is believed that excessive irrigation has induced a large number of loess landslides in this area. However, these loess landslides responses to hydrological changes have still not been well understood. Therefore, 43 boreholes and 51 2D Electrical resistivity tomography (ERT) profiles with a total length of 40 km have been investigated to analyze the hydrological characteristics for the whole terrace and characterize the effects of hydrological changes on the occurrence of different types of loess landslides. Our main findings are as follows: (1) Three groundwater domes are found in the center and eastern part of the Heitai terrace and the groundwater table is gradually rising in the whole terrace based on the ERT results. (2) The rising rate of groundwater table at the center of the terrace is twice greater than that at the margin of the terrace and it takes approximately 4 months for irrigation water to penetrate from the top surface to the saturated layer. (3) Landslide deposits could block drainage channels of groundwater, increase the localized hydraulic gradient and result in rising of local groundwater table at the edge of the terrace. (4) The resultant hydraulic gradient impels the groundwater from the center to seep out on the eastern and southern margins and new landslides are prone to occur in the main scarp of landslides with rising groundwater table. The type and magnitude of landslides are affected by groundwater seepage and movement. In order to fundamentally control the occurrence of landslides, effective drainage system and the restrained amount of irrigation water are needed.